Real‐life use of oral disease‐modifying treatments in Austria. (22nd April 2019) - Guger, Michael; Enzinger, Christian; Leutmezer, Fritz; Kraus, Jörg; Kalcher, Stefan; Kvas, Erich; Berger, Thomas; ,
Abstract : Objectives: To compare the efficacy, frequencies and reasons for treatment interruption of fingolimod, dimethyl fumarate (DMF) or teriflunomide in a nationwide observational cohort using prospectively collected data. Materials and methods: Two cohorts of patients with relapsing‐remitting multiple sclerosis (RRMS) starting treatment with fingolimod, dimethyl fumarate or teriflunomide documented in the Austrian MS Treatment Registry (AMSTR) since 2014 and either staying on therapy for at least 12 months (12m cohort) or having at least one follow‐up visit (total cohort). The 12m cohort included 664 RRMS patients: 315 in the fingolimod, 232 in the DMF and 117 in the teriflunomide group. Multinomial propensity scores were used for inverse probability weighting to correct for the bias of this non‐randomised registry study. Results: Estimated mean annualized relapse rates (ARR) over 12 months were 0.21 for fingolimod, 0.20 for DMF and 0.19 for teriflunomide treatment, causing an incidence rate ratio (IRR) of 1.01 for fingolimod vs DMF ( P  = 0.96) and 0.92 for teriflunomide vs DMF ( P  = 0.84). No differences were found regarding the probability for experiencing a relapse, EDSS change, EDSS progression and EDSS regression, except regarding less sustained EDSS progression for 12 weeks concerning DMF vs fingolimod ( P  = 0.02). The hazard ratio for treatment interruption comparing fingolimod vs DMF was 1.03 ( P  = 0.86) and 1.07 comparing teriflunomide vs DMF ( P  = 0.77). Conclusions: In the AMSTR, there was no difference concerning ARR, probability for a relapse, EDSS change, treatment interruption, EDSS progression or regression between oral DMTs, except regarding less sustained EDSS progression for 12 weeks concerning DMF vs fingolimod.